2017
DOI: 10.1007/s11356-017-0227-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of co-composting of farm manure and biochar on plant growth and carbon mineralization in an alkaline soil

Abstract: In the present study, the effects of co-composts of biochar (BC) and farm manure (FM) on the growth of wheat (Triticum aestivum L.) and carbon mineralization in an alkaline soil were investigated. The co-composts of FM and BC were prepared at various ratios (FM:BC, FM:BC, FM:BC, FM:BC, FM:BC) using aboveground piles and were used in two separate experiments conducted simultaneously. In the plant growth trial, prepared co-composts were applied at a rate of 2% w/w and wheat was grown at two fertilizer levels (ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 40 publications
4
38
0
1
Order By: Relevance
“…Besides, the imperative role of plant growth-promoting rhizobacteria, the BC, has a high water holding capacity, ion exchange capacity, high surface area that make it an effective amendment for enhanced uptake of water and nutrients in the plants 65 – 67 . Depending upon the feedstock, biochar itself carries a significant amount of mineral nutrients 68 . The application of compost also increased the nutrient status in the soils which consequently increased the uptake of nutrient in the crops 61 .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the imperative role of plant growth-promoting rhizobacteria, the BC, has a high water holding capacity, ion exchange capacity, high surface area that make it an effective amendment for enhanced uptake of water and nutrients in the plants 65 – 67 . Depending upon the feedstock, biochar itself carries a significant amount of mineral nutrients 68 . The application of compost also increased the nutrient status in the soils which consequently increased the uptake of nutrient in the crops 61 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the imperative role of organic amendments in mitigation of drought stress by improving soil water holding capacity and availability of nutrients cannot be denied 26,27 . Biochar (BC), is a black carbon compound which is a good source of nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar (BC), is a black carbon compound which is a good source of nutrients. It is produced through pyrolysis at high temperature under low or no supply of oxygen 2729 . The physio-chemical properties of BC depend on the nature of waste material used and temperature of the pyrolysis 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on biochar research have been done in acidic soils and therefore critical lack of research on alkaline soils exists. Qayyum et al (2014) investigated the effects of an application of various biochars (1%) to alkaline soils on the germination of maize. They reported that the germination percentages ranged from 69% to 85% in different treatments, but none of the biochars caused detrimental effect.…”
Section: Figmentioning
confidence: 99%
“…Our results show that the germination percentage of pepperoncini seeds in alkaline soils substrates with 2%, 4%, 8%, and 10% biochar generally increased slightly above the control, although the increase was not significant. Qayyum et al (2014) referred significant effect of biochar (1%) application to alkaline soil on seedling shoot and root lengths. This paper shows that the height of pepperoncini in all biochar applications in alkaline soil substrates was smaller when compared to the control.…”
Section: Figmentioning
confidence: 99%